rekam medis RANCANGAN PEMBATAS BAGIAN (DIVIDER/ TAB) PADA REKAM MEDIS DI RSIA ZAINAB PEKANBARU: PEMBATAS BAGIAN (DIVIDER/ TAB) PADA REKAM MEDIS - Nur Maimun; Desri Novita Yanti; Finkha Fahira; Putri Yahya; Trisna Amalia (STIKes Hang Tuah Pekanbaru, 2022)
Kegunaan dari pembatas (divider/tab) adalah menandai antara satu riwayat layanan rawat inap dengan riwayat selanjutnya atau satu bagian tertentu dengan bagian lainnya sehingga dapat menghemat waktu dalam pencarian dokumen. Berdasarkan hasil survey tidak ada pemisahan antara rawat jalan dan rawat inap. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mempermudah petugas dalam mengakses data tiap layanan. Kegiatan pengabdian kepada masyarakat ini dilaksanakan dengan merancang pembatas divider/tab dan memberikan penyuluhan dengan tatap muka kepada petugas rekam medis di RSIA Zainab Pekanbaru. Kegiatan ini dilaksanakan selama 2 bulan (Februari – Maret), dengan peserta kegiatan 10 orang petugas rekam medis. Dari hasil rancangan, petugas dapat mengaplikasikan pembatas divider/tab dalam mempermudah pelaksanaan dokumen rekam medis. Abstract Medical record documents consist of several components, namely medical record forms, clamps and fasteners to unite paper, paper dividers between one form and another and medical record file folders, all medical record forms must be stored in a medical record folder. If in one folder the records of inpatient and outpatient are combined, then the boundaries are marked with outpatient or inpatient notes and placed before the sheets. Dividers or tabs are used to limit one episode of inpatient care to the next or one particular section to another. By using the divider it will be clearer the boundary between one episode of hospitalization with the next episode. The purpose of this service is expected to shorten the time for health workers to open the patient's recent history in the medical record file. The method used in this community service activity is in several stages, namely the first stage of preparation is a preliminary study, the second stage of implementation provides understanding, counseling, and discussion. The third stage is Diffusion of science and technology (adoption and application of science and technology). From the results of community service according to the plan, carried out with opening activities by providing an understanding from the TIM about the implementation of community service, the next activity is providing material/counseling to officers, the next stage is to design a section divider (Divider/Tab) which is used to limit one episode inpatient services with the next episode or one particular section with another, the next stage is the submission of the results of the TIM design to the hospital, namely to the medical record officer. It is hoped that the results of the design can always be applied because medical records are valid documentation and evidence and maintain and maintain the contents of patient documents.